Evaluating a virtual facilitation workshop with antimicrobial stewardship teams within a cluster randomized stepped-wedge trial - Sara Malone; Kelly Bono; Jacqueline M. Saito; Shawn Rangel; Jingxia Liu; Jason G. Newland; Virginia McKay (BMC, 2024)
Abstract Background Antimicrobial stewardship programs (ASP) often function naturally as facilitators within clinical hospital settings, by working with individuals and teams to reduce unnecessary antibiotics. Within implementation science, facilitation has been studied and evaluated as an implementation strategy that can accelerate and improve fidelity to implementation efforts. This study describes a novel, virtual facilitation strategy developed and served as an intervention within the optimizing perioperative antibiotics for children trial (OPERATIC trial). This paper: (1) describes ASP team's preferences for and use of a facilitation workshop and (2) describes sustained use of facilitation skills throughout the study period. Methods Study participants included antimicrobial stewardship team members from the nine children's hospitals that participated in this study and completed facilitation training. All individuals who completed facilitation training were asked to evaluate the training through an online survey. Additionally, site leads were interviewed by the site coordinator every other month and asked about their team's use of facilitation skills throughout the rest of the study period. Survey data were managed and coded in R, and qualitative interview data were analyzed using rapid methodology. Results 30 individuals, including both physicians and pharmacists, completed the evaluation. Individuals largely rated themselves as novice facilitators (53%). Individuals reported satisfaction with virtual facilitation and identified different components of the workshops as valuable. An additional 108 interviews were performed throughout the study period. These interviews found that facilitators reported using all skills throughout the study period and described varied use of skills over time. All nine sites applied facilitation strategies, team building techniques, and communication/conflict skills at some point during the intervention phase. Conclusion We describe the use of virtual facilitation as an acceptable and appropriate strategy to enhance facilitation skills for ASP teams working to reduce unnecessary postoperative antibiotics. Participants reported different useful components of facilitation training and described using differing facilitation skills throughout the trial. Overall, the use of facilitation skills continued throughout the duration of the study period. This paper outlines how facilitation training can be conducted virtually in a way that is feasible and acceptable to clinicians. Trial registration NCT04366440, April 24, 2020.